The Evolution of Performance Management System Research: A Bibliometric Analysis of Sustainability, Digital Transformation, and Competitive Advantage - Suhardi; Rahmad Firdaus (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
The increasing complexity of global business competition, digital transformation, and sustainability pressures has encouraged organizations to adopt more adaptive and strategic Performance Management Systems (PMS). PMS is no longer limited to traditional performance evaluation but has evolved into an integrated system that supports organizational effectiveness, innovation, sustainability, and competitive advantage. Despite the rapid growth of PMS studies, the existing literature remains fragmented and lacks a comprehensive understanding of its intellectual structure, thematic evolution, and emerging research trends. Therefore, this study aims to analyse the development and research trends in PMS using a bibliometric approach. This study employed a quantitative bibliometric approach using VOSviewer to visualise and analyse scientific publications related to Performance Management Systems. Data were collected from Google Scholar, Crossref, and ScienceDirect. A total of 3,000 documents were initially identified, and after applying the PRISMA screening process, 700 relevant articles were selected for analysis. The study utilized co-occurrence analysis, network visualization, overlay visualization, and density visualization to identify dominant themes, conceptual relationships, and emerging topics. The findings indicate that performance management systems, firm performance, competitive advantage, management systems, and SMEs are the most dominant research themes. The study also reveals a significant shift from traditional performance evaluation toward sustainability-oriented and technology-driven management systems. Emerging themes such as ESG performance, green innovation, artificial intelligence, optimization, and digital transformation have gained increasing attention in recent years. This study contributes theoretically by providing a comprehensive intellectual mapping of PMS research and identifying future research directions related to sustainability, ESG integration, and intelligent performance management systems.